Societeit de Harmonie: European Elite Entertainment Center In the 19th Century in Batavia - Artyas, Yasmin; Warto, Warto (History Department, Semarang State University and Historian Society of Indonesia, 2019)
Major cities in Indonesia generally have landmarks or special features that symbolize the uniqueness and beauty of the city in question. One of the most important landmarks of the colonial city is the societeit building as an entertainment center. This study examines the function and role of Societeit de Harmonie in Batavia in the 19th century in the midst of the heterogeneous and multiethnic life of the Batavian city of Batavia. Through the study of documents and archives, the results of this study show that Societeit de Harmonie is the greatest building compared to other societeit buildings in Batavia in the 19th century. Therefore, this building is known by all citizens of the city although who can access and utilize this building is only limited. Only the European elite can enter and use the Societeit de Harmonie building. The presence of the place of entertainment also represents the entry of new values (West) that color and becomes an important part of the cultural development of the next city Batavia. These Western values are coupled with local values practiced by indigenous peoples living in the corners of the city of Batavia. The lifestyles of Europeans who lived in Batavia during the nineteenth century can be identified from their activities when gathered in the Societeit de Harmonie.Ã‚Â Kota-kota besar di Indonesia pada umumnya memiliki landmark atau ciri khusus yang menjadi lambang keunikan dan keindahan kota yang bersangkutan. Salah satu landmark kota colonial yang terpenting adalah gedung societeit sebagai pusat hiburan. Penelitian ini mengkaji fungsi dan peran Societeit de Harmonie di Batavia pada abad ke-19 di tengah-tengah kehidupan masyarakat kota Batavia yang heterogen dan multietnis. Melalui studi dokumen dan arsip-arsip sezaman, hasil penelitian ini menunjukkan bahwa Societeit de Harmoni merupakan bangunan termegah dibandingkan bangunan societeit lainnya di Batavia pada abad ke-19. Oleh karena itu, bangunan ini dikenal oleh seluruh warga kota meskipun yang dapat mengakses dan memanfaatkan bangunan ini hanya kalangan terbatas. Hanya golongan elit Eropa saja yang dapat masuk dan menggunakan gedung Societeit de Harmonie. Kehadiran tempat hiburan itu juga merepresentasikan masuknya nilai-nilai baru (Barat) yang mewarnai dan menjadi bagian penting dari perkembagan budaya kota Batavia selanjutnya. Nilai-nilai Barat ini bersanding dengan nilai-nilai local yang dipraktikkan masyarakat pribumi yang tinggal di sudut- sudut kota Batavia. Gaya hidup orang-orang Eropa yang tinggal di Batavia selama abad ke-19 dapat dikenali dari aktivitas mereka ketika berkumpul di Societeit de Harmonie.Ã‚Â